2002
DOI: 10.1002/tera.10039
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐disease continuum for 2‐chloro‐2′‐deoxyadenosine (2‐CdA), a prototype teratogen: Induction of lumbar hernia in the rat and species comparison for the teratogenic responses

Abstract: 2-CdA produced similar ocular defects in the rat and mouse, although the incidence was much lower in the former species. In contrast, the drug-induced lumbar hernia was only seen in the rat. These apparent disparities were not readily explained by species differences in pharmacokinetic parameters. the similarities between the teratological features of 2-CdA-induced lumbar hernia in the rat and the clinical description of lumbocostovertebral syndrome, however, may provide a key to unlock the etiology of this ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…13 Purine analogues are classified as pregnancy class D drugs because teratogenic effects and fetal mortality were observed in animal studies. 6 However, we were unable to find data regarding use of cladribine in gestating women.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…13 Purine analogues are classified as pregnancy class D drugs because teratogenic effects and fetal mortality were observed in animal studies. 6 However, we were unable to find data regarding use of cladribine in gestating women.…”
Section: Discussionmentioning
confidence: 88%
“…The therapeutic efficacy, teratogenicity, and maternal toxicities of purine analogues and rituximab in pregnancy are poorly defined. 6,7 Orlowski published the first report of successful pregnancy outcome after treatment of HCL with cladribine, suggesting that fertility may be preserved in some female patients exposed to purine analogues. 8 However, to our knowledge this is the first report of a favorable outcome in a pregnant HCL patient treated sequentially with a monoclonal antibody (rituximab) followed by a purine analogue (cladribine).…”
Section: Introductionmentioning
confidence: 99%
“…Any adverse event at this stage can result in defective formation of somites and their differentiation into vertebrae, ribs, and muscles of trunk [3]. To better delineate the embryogenesis of the defect, animal model has been constructed-2-chloro-2′-deoxyadenosisne-exposed Sprague-Dawley rats [4]. The acquired lumbar hernia can be owing to infection, trauma, postsurgical, tumor, and other.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown a teratogenic risk to the fetus with an increased likelihood of fetal malformations in mice [145]. The FDA rated cladribine in its currently approved parenteral form as pregnancy category D (there is positive evidence of human fetal risk, but the benefits may outweigh the risks).…”
Section: Specific Safety and Tolerabilitymentioning
confidence: 98%